2019
DOI: 10.3389/fpsyt.2019.00092
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder in Victims of Sexual Assault With Pre-assault Substance Consumption: A Systematic Review

Abstract: Background: Post-traumatic stress disorder (PTSD) and substance consumption commonly co-occur in victims of sexual assault. Substance consumption can occur pre- andi/or post-assault. Pre-assault substance consumption may have an impact on the subsequent development of PTSD. This review aims to provide an overview of current understanding of the effects of acute substance intoxication and chronic pre-assault problematic substance use on symptoms of PTSD amongst individuals who were victims of sexual assault.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 123 publications
(181 reference statements)
5
15
0
1
Order By: Relevance
“…Specifically, at the 6‐month posttreatment assessment, substance‐involved SA was associated with a higher level of residual PTSD symptom severity compared to non–substance‐involved SA. This finding builds upon prior research in samples unselected for treatment (Gong et al., 2019) and suggests that although evidence‐based treatment works to substantially reduce PTSD symptoms following substance‐involved SA, residual PTSD symptoms can be relatively more persistent when substances are involved in sexual trauma.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Specifically, at the 6‐month posttreatment assessment, substance‐involved SA was associated with a higher level of residual PTSD symptom severity compared to non–substance‐involved SA. This finding builds upon prior research in samples unselected for treatment (Gong et al., 2019) and suggests that although evidence‐based treatment works to substantially reduce PTSD symptoms following substance‐involved SA, residual PTSD symptoms can be relatively more persistent when substances are involved in sexual trauma.…”
Section: Discussionsupporting
confidence: 70%
“…Given that alcohol is the most common substance involved in SA (Kilpatrick et al., 2007), a survivor's memory of a substance‐involved SA may also be impaired (White, 2003). Finally, recovery following substance‐involved SA may follow a unique pattern, with fewer initial PTSD symptoms but a slower recovery relative to non–substance‐involved SA (Gong et al., 2019).…”
mentioning
confidence: 99%
“…The blunted drinking phenotype of NOV males here may model the subpopulation of individuals who drink less alcohol following PTSD onset (McFarlane, 1998). In fact, in some human studies, alcohol use before trauma was found to be associated with lower PTSD symptoms acutely post-trauma (Gong et al, 2019;Kaysen et al, 2011;McFarlane et al, 2009). The reduced drinking of alcohol-experienced NOV males might reflect anhedonia, decreased ethanol reward, or diminished instrumental conditioning.…”
Section: Discussionmentioning
confidence: 78%
“…The greater duration of treatment, in combination with the findings of a number of longitudinal studies, suggests that PTS arising from DFSA may be treatment refractory. Consistent findings indicate that DFSA may be associated with less severe acute stress symptomatology (Jaffe, Blayney, Bedard-Gilligan, & Kaysen, 2019 ; Jaffe, Hahn, & Gilmore, 2019 ) and shows a pattern of initially lower PTSD severity but a more chronic course of symptoms (Gong, Kamboj, & Curran, 2019 ). In their longitudinal study, Kaysen et al ( 2010 ) assessed PTSD symptom clusters in a community sample of 60 women at 2–5 weeks post-assault.…”
Section: Characteristics Of Drug-facilitated Sexual Assaultmentioning
confidence: 90%
“…Research has demonstrated the treatment-refractory nature of DFSA PTS, including that survivors require significantly more sessions of MH treatment than NDFSA and have more severe residual PTSD post-treatment (Gong et al, 2019 ; Jaffe et al, 2021 ; Kaysen et al, 2010 ; Richer et al, 2017 ; Russell & Curran, 2002 ). The first aim of the present study was to explore reasons for DFSA being treatment-refractory by (1) quantitatively comparing DFSA-I, DFSA-V, and NDFSA survivors to see whether specific differences in sociodemographics, assault characteristics, prior sexual trauma, and substance use exist between groups; (2) quantitatively comparing post-trauma PTSD and depression symptoms (PTS) among the three SA groups, with hypotheses of fewer symptoms for DFSA given the early post-assault assessment timeframe in the present study and prior research indicating fewer PTS early on for DFSA; and (3) qualitatively identifying and comparing among the three SA groups, emergent treatment themes in trauma cognitions and treatment foci from the study clinic’s psychotherapy records.…”
Section: Current Study Rationale and Aimsmentioning
confidence: 99%